A Century Apart - Birgir Hrannar Stefánsson 1982- (2014)
Læst til 10.3.2022 Iceland and China are two nations situated almost at the opposite side of the globe. In this thesis, I am taking two examples of media coverage on China; the writings of Ólafur Ólafsson are compared with the discussion in Akureyri Vikublað regarding Huang Nubo. Ólafur Ólafsson was a pioneer of intercultural communication between Iceland and China in the early 20th century. Working as a missionary in China he sent home letters published through the magazine Ljósberinn and later on these writings became the foundation for his two books, Mission on China and 14 Years in China. Through those writings Ólafur Ólafsson created one of the first images of China in the Icelandic collective consciousness. Akureyri Vikublað, a local weekly newspaper edited by Björn Þorláksson, was first published during the fall of 2011. At a very similar time the interest of Huang Nubo in Grímsstaðir á Fjöllum became public, sparking reactions both locally and internationally. Akureyri Vikublað published material regarding this matter through sent-in articles, interviews and news articles. Here, the image, perception and coverage of China and the Chinese people under discussion within these two main media sources will be compared leading to the conclusion that the image portrayed today, as it was almost a century ago, is tainted by stereotypes, insularity and xenophobia.